A sociology of constitutions constitutions and state legitimacy in historical-sociological perspective - Thornhill, C. J. (Christopher J.), 1966- (Cambridge studies in law and society., 2011)
"Using a methodology that both analyzes particular constitutional texts and theories and reconstructs their historical evolution, Chris Thornhill examines the social role and legitimating status of constitutions from the first quasi-constitutional documents of medieval Europe, through the classical period of revolutionary constitutionalism, to recent processes of constitutional transition. A Sociology of Constitutions explores the reasons why modern societies require constitutions and constitutional norms and presents a distinctive socio-normative analysis of the constitutional preconditions of political legitimacy"--